Upaya Meningkatkan Hasil Belajar Kesebangunan melalui Pembelajaran Matematika Realistik - Musrifah Musrifah (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2020)
The purpose of this research is to improve student activity, student concept understanding, and problem solving competencies on similirity trought realistic mathematic education. This research is applying on nineth E grade of MTs Negeri 2 Temanggung. This research is conducted on two cycles. Each cycle consisted of three meetings that first meeting the students presented a problem relating to similirity, at the second meeting the students facilatated students to construct the consept of similarity, at the third meeting the students served back a problem that aplication of similarity.Data obtained in this research is data activity of students in learning, the values of knowledge and skills. The data were analiyzed by using a description comparation techniques. The results of this research are active students in the first cycle of 69,4% increase to 94,4% in the second cycle, the understanding of similarity concept in first cycle of 76% increase 87% in the second cycle, and problem solving competencies on first and second cycle reach 68%.